Pengaruh Koordinasi, Komunikasi Interpersonal dan Kompetensi terhadap Kinerja Pegawai Satuan Kerja Pengembangan SPAM Provinsi Sumsel - Suci Rachma Sari; Luis Marnisah; Harsi Romli (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
The research purpose was to determine the effect of coordination, interpersonal communication and competence on the employees performance of the SPAM Development Unit in South Sumatra Province. The collected data was primary data with 50 respondents as the sample. The quantitative data was displayed in the form of table and analyzed using Statistical Product and Service Solutions (SPSS) software version 24.0. The analysis results revealed that: (1) it was obtained a significance level of 0.001>0.05 and t. 1.750<t.table 2.0086 it therefore can be concluded that there was a significant effect between coordination and performance; (2) it was obtained a significance level of 0,000<0,05 and t. 1,401<t. Table 2.0086 it hence can be concluded that there was a significant effect of interpersonal communication on performance; (3) it was obtained a significance level of 0,000<0,05 and t. 4,384> t. Table 2,0086, it then can be concluded that there was a significant effect of competence on performance and; (4) it was obtained a significance level of 0,000 <0.05 and F. count 23,044> F. table 1.599. It ultimately can be concluded that there was a significant effect coordination, interpersonal communication, and competence simultanously on the employees performance of the SPAM development unit in South Sumatra Province.